Energy-enhanced dimension eight SMEFT effects in VBF Higgs production - Assi, Benoît; Martin, Adam (The journal of high energy physics, 2025)
A bstract We study Higgs boson production via vector boson fusion at the LHC, focusing on the process pp → H + jj and capturing the leading energy-enhanced contributions within the Standard Model Effective Field Theory (SMEFT) up to order 1 / Λ 4 . Employing energy-scaling arguments, we predict the magnitude of each higher-dimensional operator’s contribution. Utilizing the geometric formulation of SMEFT, our analysis incorporates dimension-eight operators not previously considered. We find that the kinematics of vector boson fusion — characterized by two highly forward jets — tend to suppress contributions from higher-dimensional operators, requiring a lower scale Λ for SMEFT effects to become observable. This suggests that the SMEFT remains valid for lower Λ than expected. Combined with the fact that LEP constrains the dimension-six operators with the most considerable impact on vector boson fusion, a regime exists where dimension-eight operators can have significant effects. In many cases, these dimension-eight operators also influence associated production processes like pp → HV ( jj ), though differences in analysis cuts and kinematics mean this is not always the case. Our findings provide insights that could refine the search for SMEFT signals in collider experiments.